Facilitating Students' Verbal Creativity in EFL Writing Course - M. Ali Ghufron; Siti Ermawati (Universitas Muhammadiyah Semarang, 2018)
This article reported a pedagogical attempt to facilitate students' verbal creativity (hereafter: VC) in EFL writing course. This study was aimed at (1) providing students with learning activities that would promote students' VC; (2) promoting students' VC in EFL writing class; and (3) revealing students' perception towards the implementation of the pedagogical attempt in promoting students' VC. To achieve the aims, a collaborative action research was employed. The subject of this study was 30 of the second-grade students of English Education Department in a private university in East Java, Indonesia. The data in this study was taken from class observation, VC test, and in-depth interview. The results show that (1) the nine-learning-step proposed by Avila (2015) was implemented. Those nine steps are remembering English grammar and structure, creating a fictional story, promoting creative writing, boosting vocabulary through screen writing, sharing a speech, circle life, drawing and speaking, asking and answering questions, and asking the students to create their own activities. (2) From the VC test, it was also revealed that through Avila's (2015) nine-learning-step, the students’ VC are facilitated and promoted. (3) The students also have positive attitude and positive feedback towards the implementation of the nine-learning-step. The findings of this study might have implications to EFL writing teachers and students.